The Development Of Gamification-Based Learning Media “AKUBI: Akuntansi Biaya (Cost Accounting)” at SMK Muhammadiyah 2 Malang - Firdausi, Fina Melika; Putri, Sheila Febriani (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2025)
Technological advances in the Society 2.0 era require educators to be able to create learning media that is integrated with digital technology. Observations and interviews at SMK Muhammadiyah 2 Malang revealed that there were several problems faced, especially in the Accounting subject, including a lack of variety in learning media, Cost Accounting material which was classified as difficult causing students to be unmotivated to learn, and the tendency of students to play with gadgets when learning taking place. This research aims to develop